Effect of ectopic high expression of transcription factor OCT4 on the “stemness” characteristics of human bone marrow-derived mesenchymal stromal cells - Guo, Xiaoping (Stem Cell Res Ther, 2019)
OBJECTIVE: To investigate the effect of ectopic high expression of OCT4 on the stemness characteristics of bone marrow-derived mesenchymal stromal cells (BM-MSCs). METHODS: BM-MSCs were collected from three de novo acute lymphoblastic leukemia (ALL) and three aplastic anemia patients (AA), which were cultivated by the whole bone marrow adherent method. Surface markers of BM-MSCs were analyzed by flow cytometry (FCM); meanwhile, growth characteristics were observed with a phase contrast microscope, and population doubling time (PDT) was calculated. The optimal generation cells (P4) were used for the subsequent experiments. Recombinant plasmid pcDNA3.1-OCT4 was constructed and transferred into ALL MSCs by liposome transfection. The cells with stable and high expression of OCT4 were selected by G418 resistance screening and subcloning, of which the expression of OCT4 was verified by FCM, cellular immunofluorescence assay (CIFA), and RT-PCR. The expression of stemness-related transcription factors (TFs) (NANOG, SOX2) and the embryonic stem cell (ESC)-related surface markers (SSEA4, TRA-1-60, and TRA-1-81) were analyzed by FCM, RT-PCR, and CIFA. Embryonic body (EB) formation was performed with the above cells, and triembryonic differentiation marker genes were evaluated by RT-PCR. RESULTS: The primary passage of AA MSCs grew more slowly and had longer PDT (16 days on average) than ALL MSCs (10 days on average). AA MSCs presented the same typical morphology and similar expression levels of specific mesenchymal markers as ALL MSCs, whereas the latter had a much better proliferative capacity in P4 cells (P < 0.05). Besides, the expression levels of surface markers in ALL MSCs were slightly higher than that in AA MSCs in P4, P7, and P10 cells (P < 0.05). Cell lines with stable and high expression of OCT4 were successfully established from ALL MSCs, which were confirmed by CIFA, FCM, and RT-PCR. Compared with untransfected parental MSCs, the mean expression levels of TFs in OCT4 overexpression MSCs were increased from 0.63 ± 0.37% to 39.39 ± 1.85% (NANOG) and from 14.34 ± 2.44% to 91.45 ± 4.56% (SOX2). The average expression levels of ESC surface markers were increased from 3.33 ± 2.35%, 1.59 ± 1.29%, and 1.46 ± 0.86% to 84.98 ± 9.2%, 57.28 ± 6.72%, and 75.88 ± 7.35% respectively for SSEA-4, TRA-1-60, and TRA-1-81, which were confirmed by CIFA analysis. Moreover, the OCT4 overexpression MSCs could form EBs ex vivo and express ectoderm (TUBB3, WNT1), mesoderm (Brachyury, TBX20), and endoderm (SPARC) genes. CONCLUSION: Ectopic high expression of transcription factor OCT4 in BM-MSCs may drive them to grow as ESC-like cells with “stemness” characteristics. Single OCT4 transfection can upregulate the expression of other stemness-related transcription factors such as NANOG and SOX2.